INVESTIGATION OF THE COASTALLY TRAPPED WAVES IN THE SOUTH OF INDONESIAN ARCHIPELAGO - Napitupulu, Asmi Marintan; Pujiana, Kandaga; Priono, Bayu (Marine Research in Indonesia, 2010)
Analysis of sea level data derived from Jason-1 altimetry satellite reveals the basic characteristics of a coastally trapped wave along the waveguide in the south of Indonesian archipelago. The most robust signatures of the trapped wave are recorded recurrently in the months of May-June. Hovmoller and coherence analysis synonymously agree that the wave propagates at a speed of 2.8-2.9 m/s towards the eastern end of the waveguide. The trapped wave is dependent upon the stratification regime, and a Wentzel-Kramers-Brillouin (WKB) analysis on the stratification profile inferred from several CTD casts indicates that the trapped wave may be classified as a first mode baroclinic wave.